EFFECTIVENESS OF SECRETOLYTIC THERAPY IN REHABILITATION PROGRAM IN FREQUENTLY AILING CHILDREN - V.V. Kiselev; M.G. Lukashevich ("Paediatrician" Publishers LLC, 2008)
A problem of rehabilitation of frequently ailing children (FAC) is one of the actual problems in pediatrics. Disorders of mucosal immunity, depending on different factors including the state of mucociliary transport, play important role in formation of FAC group including patients with recurrent episodes of obstructive bronchitis. Morphological and functional unity of mucous tunic of respiratory tract allows determining the state of mucociliary clearance and effectiveness of secretolytic therapy by the state of mucosal tunic of nose and nasopharynx (it is the most accessible mucosal tunic for the objective examination). Specified rates of time of mucociliary transport in different groups of FAC are presented in this article. An effectiveness of mucoregulatory medication ambroxol in complex treatment of FAC with adenoids and recurrent episodes of obstructive bronchitis, and advisability of its prolonged (14-18 days) use for the recovery of disturbed system of mucociliary transport were described in this article. Key words: frequently ailing children, somatotype, mucociliary clearance, treatment.